1939
DOI: 10.1002/jcp.1030140104
|View full text |Cite
|
Sign up to set email alerts
|

The pineal eye of the lizard (Anolis carolinensis), a photoreceptor as revealed by oxygen consumption studies

Abstract: Numerous investigations have been carried out in an effort to determine the significance of the pineal eye as a photoreceptor. Francotte (1897) cauterized the eyes of the lizard Anguis fragilis and tested the receptive functions of the pineal eye. His results, while inconclusive, suggest that this organ may act as a light receptor in this species of lizard. Nowikoff ('07) studied the effect of light on the pineal eye in the lizards Lacerta agilis and Anguis fragilis and showed that the movement of pigment gran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1944
1944
1990
1990

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Parietalectomy, however, has not been conclusively shown to alter metabolic rate, although many factors such as season have not been taken into account in the few studies reported. Clausen & Mofshin (1939) found that the oxygen consumption of lizards (Anolis carolinensis) was lower in normal animals exposed to darkness than in those exposed to light. Various combinations of surgical procedures including parietalectomy, eye enucleation, and covering the dermal photoreceptors, elevated the oxygen consumption measured in darkness.…”
Section: Pineal Complex Thyroid Activity and Other Hormonesmentioning
confidence: 98%
“…Parietalectomy, however, has not been conclusively shown to alter metabolic rate, although many factors such as season have not been taken into account in the few studies reported. Clausen & Mofshin (1939) found that the oxygen consumption of lizards (Anolis carolinensis) was lower in normal animals exposed to darkness than in those exposed to light. Various combinations of surgical procedures including parietalectomy, eye enucleation, and covering the dermal photoreceptors, elevated the oxygen consumption measured in darkness.…”
Section: Pineal Complex Thyroid Activity and Other Hormonesmentioning
confidence: 98%
“…Reptilian physiologists have seldom stated the time of day at which they made their measurements, and have not, as a rule, specified light conditions during their experiments. The paper on light effects by Clausen and Mofshin ( 1939) and numerous studies of cyclical activity in reptiles (Hoffman 1957, Evans 1966 as well as studies of cyclic changes jn metabolism of other animals (for example Heusner 1956) indicate that significant differences may be involved. Such details, though of little significance in documenting the long range effect of size, are nevertheless of particular concern when comparing nocturnal and diurnal species, or hibernating versus nonhibernating individuals.…”
mentioning
confidence: 99%
“…RMRs measured in Anolis carolinensis resting in the light were found to be 50% greater than those measured in the dark (Claussen and Mofshin 1939), so that a minimum FRMR index would be 1.25, considering an animal spending half the day in the dark, half in light. Bartholomew and Tucker ( 1963) reported minimal and maximal RMRs measured in Amphibolus barbatus which differ by a factor of about three.…”
Section: Assessment Of Total Daily Energy Expenditurementioning
confidence: 83%